DYSLIPIDEMIA AND FACTORS RELATE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS EXAMINATION AT CLINIC 360 LE HOAN-THANH HOA (Vietnam Journal of Community Medicine, 2026)
Objective: Determine the rate of dyslipidemia (RLLM) and some factors related to dyslipidemia in patients with type 2 diabetes mellitus. Subjects and methods: Conduct a cross-sectional descriptive study on 164 patients with type 2 diabetes melitus examined at 360 Le Hoan General Clinic - Thanh Hoa, from March 2025 to September 2025.Results: 103 male patients (62.8%) and 61 female patients (37.2%), average age: 58.8 ± 10.5 (From 32 - 78 years old), the age group from 51 to 70 years old accounts for 67.7%. The overall rate of dyslipidemia is 83.5%, of which simple dyslipidemia accounts for 12.2%, mixed dyslipidemia accounts for 71.3%. In Lipid components, Total Cholesterol increased from mild to high 53.7%, LDL-C increased from high to very high 60.3%, Triglyceride increased high and very high 75%, HDL-C decreased 17.1%. Factors such as BMI, duration of diabetes and HbA1C index were positively correlated with dyslipidemia in patients with type 2 diabetes with statistical significance with p values of 0.022; 0.003 and 0.050, respectively. Conclusion: Type 2 diabetes and RLLM have a close relationship and bidirectional impact on each other, characterized by increased Triglyceride and LDL-C, decreased HDL-C. Good control of both blood sugar and blood lipids is a key factor in preventing serious events in patients with type 2 diabetes.
Keywords: Dyslipidemia, Type 2 diabetes mellitus, Associated factors.